1991
DOI: 10.1002/pi.4990250409
|View full text |Cite
|
Sign up to set email alerts
|

Chain‐extended polyurethanes—Synthesis and characterization

Abstract: Thermoset polyurethane (PU) elastomers were prepared using hydroxyl‐terminated polybutadiene (HTPB), toluene diisocyanate (TDI) and hexamethylene diisocyanate (HMDI). The effects of various diamines and diols on the mechanical and thermal properties of polyurethanes are discussed. The average molecular weight between crosslinks (M̄/c) was determined by swelling studies. The properties imparted by the extenders are explained on the basis of the groups present in the diamines and the number of methylene carbons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…(2) shows that the intensity of the damping peak decreases with increasing degree of crystallinity; we found the same trend in this study.…”
Section: Dmta Studiessupporting
confidence: 87%
See 1 more Smart Citation
“…(2) shows that the intensity of the damping peak decreases with increasing degree of crystallinity; we found the same trend in this study.…”
Section: Dmta Studiessupporting
confidence: 87%
“…One of the different methods for improving the thermal stability of PU is tailoring its molecular structure by using variable raw materials. This is because the thermal stability and mode of decomposition of polymers are largely dependent on the chemical structure of chain segments and also the nature of intermolecular hydrogen bonding [2] . Mass loss during the degradation process in the absence of well selected raw materials and thermally stable blocks, is maybe due to the chain scission and loss of intermolecular bonds between the polymer chains leading to the elimination of degraded products and low molecular weight components [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the molecular weights of FPCPU‐P and FPCPU‐H are lower than that of FPCPU‐T and FPCPU‐M (Table I). It has been confirmed that the reactivity of the secondary hydroxyl groups of PPG with diisocyanate was lower than that of the primary hydroxyl groups of the polyether because of the hindrance of the methyl side chain 29. In addition, Nakaya et al30 obtained the lower molecular weights of PUs containing polycarbonate diols compared with polyether diols in the same synthetic condition.…”
Section: Resultsmentioning
confidence: 93%
“…Several studies have examined the effects of trimerization and crosslinking on the physical and mechanical properties of copolyurethane networks. [3][4][5][6][7][8][9][10][11][12] Although some of these studies have focused on the thermal properties and effects of crosslinking on the swelling behavior and sol/gel fraction of PUIRs, there have been few fundamental studies on PUIRs with a base of toluene diisocyanate (TDI) and poly(propylene glycol) (PPG). 13,14 In this article, the catalyzed synthesis of PUIRs on bases of TDI and PPG in the presence of the organometalic catalysts dibutyltin dilaurate (DBTDL) and ferric acetylacetonate (FeAA) is studied.…”
Section: Introductionmentioning
confidence: 99%